Labdane diterpenoids from Marrubium vulgare. (September 2015) - Masoodi, Mubashir; Ali, Zulfiqar; Liang, Shuang; Yin, Hongquan; Wang, Wei; Khan, Ikhlas A.
Graphical abstract: Highlights: Phytochemical investigation of the whole plant of Marrubium vulgare is discussed. Two new labdane diterpenoids were isolated. Structure elucidation was achieved by means of NMR spectral data and mass. Antimicrobial activity of isolated diterpenoids is described. Abstract: Phytochemical investigation of the whole plant of Marrubium vulgare L. (Lamiaceae) resulted in isolation and characterization of two new labdane diterpenoids, 12( S )-hydroxymarrubiin and 3-deoxo-15-methoxyvelutine C and 11 known compounds, marrubiin, peregrinin, thessaline D, marrubinone B, deacetylvitexilactone, verbascoside, leucosceptoside A, martynoside, anisofolin A, terniflorin, and apigenin. Structure elucidation of the isolated compounds was determined by using spectroscopic techniques and HRESIMS. 12( S )-Hydroxymarrubiin, marrubiin, peregrinin, and marrubinone B, exhibited no antimicrobial activity up to 20 μg/mL against ten strains.